Mud Dauber Nests as Sources of Spiders in Mercury Monitoring Studies. (10th March 2021) - Hannappel, Madeline P.; Chumchal, Matthew M.; Drenner, Ray W.; Kennedy, Jim; Barst, Benjamin D.; Castellini, J. Margaret
Abstract: Identifying ecosystems where biota may be contaminated with hazardous levels of methylmercury (MeHg) is a challenge. One widely used approach for determining site‐specific MeHg contamination is to monitor MeHg contamination in sentinel species. Terrestrial shoreline spiders that consume emergent aquatic insects (e.g., midges and mayflies) have been proposed as sentinels of MeHg contamination of aquatic ecosystems. The purpose of the present study was to determine whether a novel sampling technique, collection of spiders from nests of mud dauber wasps (Sphecidae), would be an efficient method for capturing MeHg‐contaminated shoreline spiders for use as sentinels in ecological risk assessments. Mud dauber nests were collected near the Clear Fork of the Trinity River in Fort Worth, Texas (USA) on 3 dates from 4 human‐made structures. Nests contained 627 unconsumed spiders from 5 families: Araneidae, Salticidae, Thomisidae, Oxyopidae, and Theridiidae. Methylmercury concentrations ranged from 12.2 to 56.3 ng/g wet weight in Thomisidae and Araenidae, respectively. Methylmercury concentrations of the spiders were generally low relative to risk thresholds for adult birds, but a few families of spiders could pose a risk to nestlings. Although mud dauber nests have been recognized as a source of spiders for biodiversity studies, the present study is the first to demonstrate the potential use of spiders collected from mud dauber nests for ecotoxicology studies. Environ Toxicol Chem 2021;40:1335–1340. © 2021 SETAC